Tolerance of F6 Red Rice Lines against Iron (Fe) Stress - Eries D Mustikarini; G Ibnu Prayoga; R Santi; Siti Khodijah; T Lestari (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2021)
Dryland area in Indonesia reaches 108.8 millions ha (69.4%) of the total dry land with the potential to expand the area of food crops reaching 7.1 million ha, which is dominated by ultisol and oxisol soil types. Plant constraint cultivation on ultisol soil types is the acidic soil pH with high Al and Fe levels. One of the efforts that can be made to cultivate plants on ultisol soil is the selection of plants that are tolerant of Fe stress. This study aimed to determine a tolerance level and F6 red rice lines that were tolerant of iron (Fe) stress in ultisol soils. The experimental design used was factorial Completely Randomized Design (CRD) consisting of 2 factors, the first factor consisted of 12 treatments (10 test lines and 2 comparison varieties) and the second factor  was iron stress with concentrations (0 ppm and 551,55 ppm). The stress was applied after 3 WAP. The stress resistance test to iron (Fe) should that all lines of red rice F6 on ultisol soils have a score of 1 which indicates the stress tolerance of Fe at a concentration of 551,55 ppm Fe. The 23A-56-30-25-12 and 23A-56-30-25-13 lines were the best lines that were tolerant of 551,55 ppm iron (Fe) stress with the highest growth and yield. The lines tested can be developed on ultisol soils because they are tolerant of Fe.